UJI PENERIMAAN KONSUMEN KOPI ARABIKA ARGOPURO DENGAN PENGOLAHAN NATURAL, HONEY DAN FULLWASH - Mahardika, Nidya Shara; Suwasono, Sony; Plus, Melinda Lady; Amilia, Winda (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Jember, 2022)
Argopuro Arabica coffee is coffee grown in Klungkung Village, Sukorambi District, Jember Regency by the Santoso Farmer Group. Klungkung Arabica coffee needs to be tested together with specialty coffee to determine consumer acceptance in order to realize the desire of Klungkung Village farmer groups to market their products throughout Indonesia and even abroad. The purpose of this study is to determine the segmentation and positioning of Arabica coffee